Neuroprotection by luteolin and gallic acid against cobalt chloride-induced behavioural, morphological and neurochemical alterations in Wistar rats (2019)
Cobalt (Co) intoxication arising from occupational exposures and ion release from metal implants has been associated with neurological alterations such as cognitive decline, incoordination and depression. The present study evaluated the mechanisms of neuro-protection exerted by Luteolin (Lut; 100 mg/kg) and Gallic acid (GA; 120 mg/kg) in Wistar rats exposed to cobalt chloride (CoCl2) at 150 mg/kg for 7 consecutive days. Results indicate that CoCl2 induced neuro-behavioural deficits specifically by decreasing exploratory activities of CoCl2- exposed rats, increased anxiety, as well as significant reduction in hanging latency. Co-treatment with Lut or GA, however, restored these parameters to values near those of normal controls. Moreover, Lut and GA prevented CoCl2-induced increases in hydrogen peroxide (H2O2), malondialdehyde (MDA) and nitric oxide (NO) in the brain, while also restoring the activities of acetylcholinesterase, glutathione S-transferase (GST) and superoxide dismutase (SOD). In addition, Lut and GA produced significant reversal of CoCl2-induced elevation in levels of serum Interleukin 1 beta (IL-1β) and Tumor necrosis factor (TNFα). Meanwhile, immunohistochemistry revealed increased astrocytic expression of glial fibrillary acidic protein (GFAP), with intense calbindin (CB) D-28k staining and pronounced dendrites in the Purkinje cells. In contrast, the CoCl2 group was characterized by decreased number of neurons expressing CB and dendritic loss. Taken together, mechanisms of luteolin and/or gallic acid protection against Co toxicity involved restoration of Ca2+ homeostasis, acetylcholinesterase and antioxidant enzyme activities, as well as inhibition of lipid peroxidation in the brain.